Immediate Impact of Kidney Transplantation on Blood Pressure Single Center Experience - Rahman, Md Anisur; Mitra, Palash; Rahim, Muhammad Abdur; Samdani, Tasrina Shamnaz; Hossain, Md Golzar; Billah, Md Mostarshid; Haque, Wasim Md Mohosinul; Mansur, Md Abul; Khoda, Md Mehfuz E (BIRDEM Medical Journal, 2016)
Introduction and Aims: Hypertension (HTN) can be either a cause or a consequence of chronic kidney disease (CKD). Kidney transplantation is the most preferred mode of treatment of end stage kidney disease (ESKD). Long term outcome of the renal allograft after kidney transplantation largely depends upon good control of blood pressure (BP). The aim of this study was to observe the status of blood pressure and anti-hypertensive requirement of the kidney transplant recipients in post-kidney transplant hospital stay period. Methods: This cross-sectional study was done in BIRDEM General Hospital from January 2007 to July 2014. A questionnaire was formed and data were collected from the hospital records. We divided the patients according to primary cause of ESKD in group 1 (due to diabetes mellitus), group 2 (due to chronic glomerulonephritis) and group 3 (patients with hypertension). Results: Total number of patients was 82, male were 56 and female were 26. Mean age was 38.49 ± 10.58 years. Most of the patients belonged to group 2 (35, 42.68%) followed by group 1 (25, 30.48%) and group 3 (22, 26.83%). After kidney transplantation both mean systolic and mean diastolic BP decreased significantly (p-value 0.000). To control BP only 9(10.98%) patients required increased dose of antihypertensive drugs after transplantation. In patients with HTN as primary disease change in number of antihypertensive drugs was not significant (p-value 0.069) unlike to the other two groups. Before kidney transplantation in only 9.76% patients BP could be kept within acceptable reference range with or without anti-hypertensive medication but after transplantation it was 68.29% with less number of drugs. Conclusion: In this study population, the blood pressure could be kept within acceptable reference range with less number of anti-hypertensive drugs during discharge after kidney transplantation. Birdem Med J 2015; 5(1) Supplement: 25-28